Prinsip dalam Berkontrak Pelaku Olahraga Sepakbola Profesional di Indonesia - Nurharsya Khaer Hanafie; Fatimah Hidayahni Amin; Ririn N. (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2021)
Legal studies have two types of research, namely normative legal research and empirical legal research. According to Peter Mahmud Marzuki, normative legal research is a process to find a rule of law, legal principles, and legal doctrines to answer the legal problems faced. Normative legal research is carried out to produce new arguments, theories or concepts as prescriptions in solving problems at hand. The research of this article aims to find out the principles of contracting for professional football players so that professional sports players in entering into a business agreement can find the contract principles contained in contracts made by professional sports players. In theory, this article will examine the extent to which contracts in civil law that apply in general can be translated into contracts for professional sports players that will apply specifically or lex specialis because they contain elements of civil and business contracts in the form of a special contract that is characterized by a contract for Professional sports players, especially football.